Outcome of Hepatoblastoma in A Low-and Middle-Income Country; Single Centre Experience from Pakistan - Manzoor, Rabiha; Ghafoor, Tariq; Arshad, Awais; Hira, Beenish; Latif, Ayesha; Khan, Fouzia (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the survival outcome of patients with hepatoblastoma (HB) treated at a tertiary care hospital of Pakistan. Study Design: A prospective cohort study. Place and Duration of Study: Pediatric oncology unit, Combined Military Hospital, Rawalpindi Pakistan from Jan 2013 to Dec 2023. Methodology: All cases of hepatoblastoma (HB) diagnosed in individuals aged up to 12 years were enrolled. The study primarily focused on documenting survival outcomes, encompassing both "overall survival (OS)" and "disease-free survival (DFS). Results: In a total of 29 patients with HB, 18(62.1%) were boys. The median age at the time of diagnosis was 1.3 years (0.8 to 2.8 years). At presentation, abdominal distension was present in all 29(100%) cases whereas palpable abdominal mass, and jaundice was present in 25(86.2%), and 9(31.0%) patients, respectively. Mortality was reported in 14(48.3%) patients. The median DFS, and OS were 18.64 months (5.27 to 47.04 months), and 0.13 months (0 to 44.00 months), respectively. Surgery emerged as a significant predictor of mortality, with a striking 15.89 times higher odds of mortality if surgery was not performed (95% CI: 1.71-147.39, p=0.015). Overall, 8-year survival was 50.0%. Eight year cumulative DFS was 59.3% for standard risk, 44.4% for high risk, and 26.7% for very high risk patients. OS was 60.0% for standard risk, 44.4% for high risk, and 40.0% for very high risk patients. Conclusion: Hepatoblastoma is a rare pediatric cancer. A very high relapse/refractory rate needs further investigation to determine the cause of failure of the treatment.